Analysis of Development through Digital Marketing in Technology 4.0 Era at 'Laksana Berkah' Potato Seed House - Yuniarsih, Yuyun; Syafariah, Anita; Rustiman, Uus; Lutfiiyani, Isni (Yayasan Sinergi Kawula Muda, 2024)
This research aims to develop a digital marketing strategy to enhance the market potential of potato seedlings at 'Laksana Berkah Potato Seed House' in Pulosari Village, Bandung Regency. The study will explore digital innovations and technologies to optimize agricultural product marketing, particularly potato seedlings, leveraging the Technology 4.0 era. As a producer and distributor of quality potato seedlings, 'Laksana Berkah Potato Seed House' faces challenges in effective marketing. The research will investigate digital marketing strategies, including e-commerce platforms, social media, websites, and mobile applications, to expand market reach and improve efficiency. Additionally, the potential of technologies such as big data analytics, artificial intelligence, and marketing automation will be explored to enhance marketing strategy effectiveness. The study will also consider the socio-economic impact of digital marketing implementation on local farmers and the regional economy. The findings are expected to offer strategic recommendations for 'Laksana Berkah Potato Seed House' and contribute to enhancing the competitiveness of the local agricultural sector in Bandung Regency.